2010
DOI: 10.1111/j.0105-2896.2009.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Subsets of migrating intestinal dendritic cells

Abstract: SummaryDendritic cells in the intestine are heterogeneous. Phenotypically different populations of conventional dendritic cells have been identified in the intestinal lamina propria, Peyer's patches, and in the draining mesenteric lymph nodes, to which these DCs constitutively migrate. Markers used to identify these populations include MHC class II, CD11c, CD8α, CD11b, and CD103. Extensive studies in rats, summarised here, which involved collection of migrating DCs by thoracic duct cannulation after mesenteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 69 publications
2
70
0
2
Order By: Relevance
“…DCs in the intestinal mucosa play a crucial role in directing immune responses to luminal antigens (20,32). Intestinal DCs can efficiently migrate to MLNs, thereby providing a critical link to adaptive T cell immunity (51).…”
Section: Discussionmentioning
confidence: 99%
“…DCs in the intestinal mucosa play a crucial role in directing immune responses to luminal antigens (20,32). Intestinal DCs can efficiently migrate to MLNs, thereby providing a critical link to adaptive T cell immunity (51).…”
Section: Discussionmentioning
confidence: 99%
“…The collection of migrating DC using this method has provided invaluable information on their phenotype and functions. It has been possible to cannulate the lymphatic vessels of a number of animal species; however, the procedure remains technically challenging and successful only for the thoracic duct in the rat and other lymph vessels in large animals (2,16,24,44). These lymph DC are a valuable reagent to study the interaction with potential vaccine antigens because they can be used directly ex vivo without extensive in vitro manipulations.…”
mentioning
confidence: 99%
“…p (a/b) < 0.05 or p (*) < 0.05 represents a significant difference between groups. (Onodera et al 2009;Milling et al 2010). These results suggested that there was a relationship between the suppression of ethanol-mediated IgA responses and the decrease in palmitoyl-ova transport to MLNs.…”
Section: Resultsmentioning
confidence: 99%